(3HMhK GdYedjGJ hGdEMUGAs - (3eMehOYdi eJhdi(B, (3YLhQs ((3GdEScfOQjI(B:s (3OGQ GdacQ GdLGeYj(B,s, 2007)
(3jVe GdGMJeGdGJ hGdGMUGA(B: (3fXQjI GdaFGJ, GdJLQHI GdYThGFjI, GdeJZjQGJ GdYThGFjI, WQb YQV GdHjGfGJ, GdebGjjS GdChdjI ddfRYI, GdebGjjS GdQFjSjI ddfRYI GdeQcRjI, HYV GdJhRjYGJ, HMhK GdYedjGJ(B: (3WQb GJNGP GdbQGQ, fXQjI GdOhGFQ, GSdhH HQJ hGSJNOGeGJ, GdHQeLI GdNWjI, eTGcd Gdfbd hGdJNUU, GdJfHDs
Keywords: (3GdEMUGA (B- (3GdeYGedGJ GdEQJHGWjI s; (3GdGMJeGdGJs; (3HMhK GdYeGdjGJs